2021
DOI: 10.3389/fimmu.2021.769204
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Methylation Analysis of Long Noncoding RNAs and mRNAs in IPEC-J2 Cells Treated With Clostridium perfringens beta2 Toxin

Abstract: BackgroundThe n6-methyladenosine (m6A) modification is present widely in mRNAs and long non-coding RNAs (lncRNAs), and is related to the occurrence and development of certain diseases. However, the role of m6A methylation in Clostridium perfringens type C infectious diarrhea remains unclear.MethodsHere, we treated intestinal porcine jejunum epithelial cells (IPEC-J2 cells) with Clostridium perfringens beta2 (CPB2) toxin to construct an in vitro model of Clostridium perfringens type C (C. perfringens type C) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…M 6 A methylation of lncRNAs in skeletal muscles of pig and Cattle-Yak has been excavated to find new candidate lncRNAs of muscle-fiber-type conversion and muscle development [32,33]. The change of m 6 A methylation of lncRNAs in IPEC-J2 cells induced by Clostridium perfringens beta2 toxin has been described [34]. However, the role of m 6 A methylation in lncRNAs in pigmentation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A methylation of lncRNAs in skeletal muscles of pig and Cattle-Yak has been excavated to find new candidate lncRNAs of muscle-fiber-type conversion and muscle development [32,33]. The change of m 6 A methylation of lncRNAs in IPEC-J2 cells induced by Clostridium perfringens beta2 toxin has been described [34]. However, the role of m 6 A methylation in lncRNAs in pigmentation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it impacts cellular antiviral capacity by modulating the protein level of MX1 [ 28 ]. Previous MeRIP-sequencing studies revealed that m6A-modified lncRNA EN_42575 was significantly altered in CPB2-group cells [ 13 ]. Here, we reported a significantly reduced expression of m6A-modified lncRNA EN_42575 in IPEC-J2 cells following treatment with the CPB2 toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, m6A modifications could affect the functions of lncRNAs in diseases through multiple regulatory mechanisms [ 12 ]. The m6A-modified lncRNAs, namely, ENSSSCG00000048701 and ENSSSCG00000048785 , have been speculated to be involved in the immune and inflammatory responses of IPEC-J2 cells by regulating their target genes to resist bacteria-induced diarrhea in piglets [ 13 ]. However, studies on the mechanisms underlying disease regulation by m6A-modified lncRNAs are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, m 6 A modification control numerous biological processes, such as metabolism, differentiation, and disease pathology [ 30 ]. Prior investigations demonstrated m 6 A as a critical contributor to host resistance of multiple pathogen/microbial infections [ 31 , 32 , 33 , 34 ]. METTL3 is a methyltransferase that accelerates m 6 A synthesis, which regulates viral replication and E. coli infection.…”
Section: Discussionmentioning
confidence: 99%